Double Murder Following Intoxication with Sedative Drugs - Vidanapathirana, M.; Gunathilake, K.M.T.B. (Forensic Medicine and Toxicology Department, 2015)
Background: Sedative drugs are important in many ways in medicolegal practice. They are used to subdue or alter the mind of a victim and also such drugs themselves can cause death. These drugs are used in robberies as well as in murder cases. Case Report: Two averagely built healthy parents were found dead on bed with deep cut injuries to neck, with minimal evidence of volitional activities and defense injuries. An involvement of a poison was suspected. The elder daughter had felt a bitter taste of the dinner and kept it in the refrigerator at that night. The dinner was sent for toxicological investigations. Causes of deaths were cut injuries to neck. At the same time, the investigators found out that the younger daughter had mixed diazepam to dinner and her boyfriend and 4 others killed the parents. A film they had watched had influenced them to initiate this incident. Conclusion: Two well-built conscious adult victims in sober state should have received at least few defense injuries or leave evidence of volitional activities. In such circumstances, intoxication with drugs or incapacitated with other means should be considered by the forensic pathologist.
Keywords: Sedative drugs; Double murder; Cut throat